Feeding ecology, daily activity budget and primatourism of schlegel’s banded langur (presbytis neglectus) (schlegel,1876) in Kota Tinggi Johor - Mohd Faudzir, Najmuddin (2019)
Schlegel’s banded langur, Presbytis neglectus, is an endemic leaf-eating monkey distributed in Johor but faced lacked of concern on its conservation aspect. It has the potential to be a primate-based tourism product called PrimaTourism (read: primate tourism) which is able to offer a sustainable approach in balancing the importance of conservation and local economic development. Yet, the data for feeding ecology and daily activity budget for P. neglectus for development of PrimaTourism are non-existent. Thus, this study aimed to document record on feeding ecology and daily activity budget of P. neglectus in Kg. Johor Lama, Kota Tinggi, subsequently transforming the data to PrimaTourism product. Scan sampling method was employed from February 2018 to February 2019 for 15 days per month during daytime from 0700 h to 1900 h. Identification of plants consumed by P. neglectus was made using dichotomous key, local name and based on published record. 29 species of plants were recorded from 18 families with leaves constitute the majority of diet (54%), followed by fruits (33%), seed (10%), and flower (3%). The Schlegel’s banded langur spent most of its time resting (43%), moving (26%), feeding (26%), socialising (4%) and doing others activities (1%). Long resting time was related to fermentation process in the gut as its major food preferences are leaves and also related to low diversity of plants consumed by P. neglectus in the area. ‘Wild Primate Peek™’ module and primate trail feature were successfully developed based on behaviour and ecology data of P. neglectus and the feedback from qualitative and quantitative survey. The potential of P. neglectus as PrimaTourism product was aligned with seven criteria of organism-based tourism proved the viability of the product. As a conclusion, based on the ecology study, feedbacks from local guides and visitors proved that both, P. neglectus and PrimaTourism are viable in Kg. Johor Lama.